Spatiotemporal Variation of Microbial Communities in the Ultra-Oligotrophic Eastern Mediterranean Sea - Haber, Markus; Roth Rosenberg, Dalit; Lalzar, Maya; Burgsdorf, Ilia; Saurav, Kumar; Lionheart, Regina; Lehahn, Yoav; Aharonovich, Dikla; Gómez-Consarnau, Laura; Sher, Daniel; Krom, Michael D.; Steindler, Laura (Frontiers in Microbiology, 2022)
Marine microbial communities vary seasonally and spatially, but these two factors are rarely addressed together. In this study, the temporal and spatial patterns of the bacterial and archaeal community were studied along a coast-to-offshore transect in the Eastern Mediterranean Sea (EMS) over six cruises, in three seasons of 2 consecutive years. Amplicon sequencing of 16S rRNA genes and transcripts was performed to determine presence and activity, respectively. The ultra-oligotrophic status of the Southeastern Mediterranean Sea was reflected in the microbial community composition dominated by oligotrophic bacterial groups such as SAR11, even at the most coastal station sampled, throughout the year. Seasons significantly affected the microbial communities, explaining more than half of the observed variability. However, the same few taxa dominated the community over the 2-year sampling period, varying only in their degree of dominance. While there was no overall effect of station location on the microbial community, the most coastal site (16 km offshore) differed significantly in community structure and activity from the three further offshore stations in early winter and summer. Our data on the microbial community compositions and their seasonality support previous notions that the EMS behaves like an oceanic gyre.